2015
DOI: 10.1097/rlu.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Imaging Sensitivity of Positron Emission Mammography and Whole-Body PET in Relation to Tumor Size

Abstract: The imaging sensitivity of PEM was higher than that of WBPET in Japanese women younger than 50 years. Positron emission mammography showed significant sensitivity in tumors smaller than 1 cm, which has been a weak point for WBPET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…PET imaging in breast cancer is most often used in the form of PET computed tomography (CT) with fluorine‐18 fludeoxyglucose ( 18 F‐FDG) to assess distant metastatic disease and to look for and monitor recurrent disease . Positron emission mammography (PEM) is also used in breast imaging, but this system has a higher spatial resolution and smaller field of view than whole‐body PET imaging and is not currently integrated with MRI for breast imaging . As such, PEM is not discussed in this review.…”
mentioning
confidence: 99%
“…PET imaging in breast cancer is most often used in the form of PET computed tomography (CT) with fluorine‐18 fludeoxyglucose ( 18 F‐FDG) to assess distant metastatic disease and to look for and monitor recurrent disease . Positron emission mammography (PEM) is also used in breast imaging, but this system has a higher spatial resolution and smaller field of view than whole‐body PET imaging and is not currently integrated with MRI for breast imaging . As such, PEM is not discussed in this review.…”
mentioning
confidence: 99%
“…With an improved resolution of PEM, some research showed that the detection rate of PEM was 2.3%, which is better than that of PET/CT (Yamamoto et al 2015(Yamamoto et al , 2016. Other research suggested that the sensitivity of PEM is significantly better than that of PET in tumors that are 20 mm or smaller in size (Eo et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…positron emission mammography (PEM) and a tomographic technique using a ring-shaped scanner (ring-shaped dbPET) [7]. PEM systems depict breast tissue via soft compression of the breast with two opposing plate-like detectors and have higher sensitivity than whole-body PET/CT [8][9][10] while ring-shaped dbPET scanners can visualise breast cancer more clearly than whole-body PET/CT [11,12]. These high-resolution breast PET systems have greater photon sensitivity and can improve spatial resolution by setting the detector close to the breast, reducing respiratory movement, and using smaller detection units with reconstruction methods that are different to those used for whole-body PET/CT.…”
Section: Introductionmentioning
confidence: 99%